PERANCANGAN DAN IMPLEMENTASI E-LEARNING SEBAGAI AKSELERASI PROSES PEMBELAJARAN DALAM PENINGKATAN MUTU AKADEMIK DI PRODI ILMU KOMPUTER FST UIN SU MEDAN - Sriani Sriani; Armansyah Armansyah; Mhd Furqan; Raissa Amanda Putri (UIN Sumatera Utara Medan, 2020)
Along with the development of technology in the current digital era, demanding all fields of industry to be able to utilize technology in its business processes, is no exception in the field of Education. In the education and service industries, providing customer satisfaction services is very important. The quality of a Study Program is largely determined by the quality of the services provided, where quality service can be identified through customer satisfaction in this case students. One of the breakthrough services by utilizing information technology that can be applied by the Computer Science study program at the Faculty of Science and Technology of North Sumatra UIN Medan, is currently applying technology-based learning with the E-Learning program